2021
DOI: 10.3389/fphar.2021.592071
|View full text |Cite
|
Sign up to set email alerts
|

Homoharringtonine Exerts Anti-tumor Effects in Hepatocellular Carcinoma Through Activation of the Hippo Pathway

Abstract: Hepatocellular carcinoma (HCC) is the most prevalent subtype of liver cancer with a mortality rate of approximately 3–6/100,000 and is the third leading cause of cancer-related death worldwide. Although several small-molecule drugs have been developed for the treatment of HCC, the choice of an agent for patients who require systemic chemotherapy at an advanced stage is still limited. The Hippo pathway is an evolutionarily conserved tumor suppressive pathway commonly dysregulated in HCC, which makes it a promis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…When tumors reached a volume of approximately 50–100 mm 3 , mice from both groups were randomly assigned to treatment with vehicle or HHT (1 mg/kg, daily gavage). The 1 mg/kg dosage of HHT used to treat the nude mice with xenograft tumors was selected according to previous studies ( Wang et al, 2021 ; Weng et al, 2018 ). Tumor volume was monitored every 3–4 days.…”
Section: Methodsmentioning
confidence: 99%
“…When tumors reached a volume of approximately 50–100 mm 3 , mice from both groups were randomly assigned to treatment with vehicle or HHT (1 mg/kg, daily gavage). The 1 mg/kg dosage of HHT used to treat the nude mice with xenograft tumors was selected according to previous studies ( Wang et al, 2021 ; Weng et al, 2018 ). Tumor volume was monitored every 3–4 days.…”
Section: Methodsmentioning
confidence: 99%
“…More studies are needed to fully understand the therapeutic potential of Hippo pathway inhibition in LGG. Similarity, the restoration of cell viability and reversal of HHT-induced hepatocellular carcinoma apoptosis were observed following treatment with XMU-MP-1 (32). Chao et al (33) reported that MST1 down-regulation promoted glioma cell proliferation and growth, while inhibiting apoptosis.…”
Section: Discussionmentioning
confidence: 58%
“…Thus, for an individual of 175 cm for 70 kg, the body surface correspond to 1.85 m 2 and the admitted dose is 4.625 mg/days or 0.07 mg/kg. The dose administrated to animal in our study (1 mg/kg) is based on the literature (Li et al, 2020; Wang et al, 2021) and is 15-fold higher than the human clinical recommendation and 4-fold below the toxic dose in mouse (Yakhni et al, 2019). Under our conditions, this alkaloid reduced REV-ERBα protein level by more than 20% at ZT9, its usual peak time in mouse hearts (Figure 2d).…”
Section: Resultsmentioning
confidence: 99%
“…For acute in vivo experiment, 11-weeks-old wild-type males were first acclimated for 2 weeks in the animal facility. On the day of the experiment, HHT 1 mg/kg, a dose chosen according to previous studies (Li et al, 2020; Wang et al, 2021), or control vehicle [0.25% DMSO in 9 g/L NaCl solution] was administrated by intraperitoneal injection at ZT5. Animals were then sacrificed at ZT9 by cervical dislocation and hearts were cut in half, flash-frozen in liquid nitrogen, and stored at −80 °C.…”
Section: Methodsmentioning
confidence: 99%